INTERNATIONAL EXAMINATIONS ENGLISH LANGUAGE TEACHERS AS A MEANS OF IMPLEMENTING THE REQUIREMENTS OF THE PROFESSIONAL TEACHER STANDARD - Yayra Rakhimova (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2021)
Currently, there is a tendency in modern Uzbek society to put forward new requirements for the education system, which is considered one of the most important components of the economic growth and well-being of the nation, as well as the stabilization of the country's social life. At the same time, in the concept for the development and modernization of national education, special attention is paid to the issue of the quality of education and its compliance with world standards. In this regard, it was announced at a video conference chaired by the President Sh. Mirziyoev that an agency for the promotion of foreign languages will be established under the Cabinet of Ministers of Uzbekistan. The agency also will conduct foreign language proficiency rankings in schools, universities, districts, cities and regions, sectors and government agencies.